2021
DOI: 10.1088/2040-8986/abfa72
|View full text |Cite
|
Sign up to set email alerts
|

Angular-momentum exchange among acoustic and optical waves at the collinear acousto-optic diffraction

Abstract: We consider collinear acousto-optic diffraction of circularly polarized optical waves at circularly polarized acoustic waves in the crystals that reveal both acoustic conical refraction and optical activity. We find that, due to the conical refraction of acoustic waves, these waves produce vector-vortex beam. In this process, the orbital angular momentum (OAM) of the conically refracted acoustic wave is transformed into the OAM of the diffracted optical wave. At the same time, the spin angular momentum of coni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The collinear AO diffraction of circularly polarized optical waves at circularly polarized acoustic waves (AWs) in the crystals that reveal both acoustic conical refraction and optical activity has been considered 12 . It has been found that, due to the conical refraction of AW, this wave produce vector-vortex beam.…”
Section: Theorymentioning
confidence: 99%
“…The collinear AO diffraction of circularly polarized optical waves at circularly polarized acoustic waves (AWs) in the crystals that reveal both acoustic conical refraction and optical activity has been considered 12 . It has been found that, due to the conical refraction of AW, this wave produce vector-vortex beam.…”
Section: Theorymentioning
confidence: 99%